Productivity and Growth Indices of Intercrops in Agri-Horti-Silvi System in Arid Rajasthan - Yadava, N D; Soni, M L; Birbal, Birbal (Annals of Arid Zone, 2016)
Mung bean (Vigna radiata (L.) R. Wilczek) and clusterbean (Cyamopsis tetragonoloba (L.) Taub.) were grown as inter crops under agri-horti-silvi system with 9-year-old plantations of citrus (Citrus aurontifolia), mopane (Colophospermum mopane) and shisham (Dalbergia sissoo) at Research Farm of Central Arid Zone Research Institute, Regional Research Station, Bikaner, during kharif 2011. Highest total biological yield and seed yield of mung bean (1412.5 and 471.3 kg ha-1, respectively) and clusterbean (1352 and 419.8 kg ha-1, respectively) was recorded in intercropping with citrus. Highest leaf area plant-1 and chlorophyll content in clusterbean (2.44 mg g-1 FW) and mung bean (2.62 mg g-1 FW) intercropped with citrus were responsible for more seed yield due to accumulation of more photosynthates in plants. Higher leaf water potential of clusterbean (-3.18 MPa) and mung bean (-3.28 MPa) was recorded in intercropping with mopane. Among different tree leaves, leaf water potential was highest in mopane (-6.99 MPa) followed by citrus (-5.51 MPa) and shisham (-3.58 MPa). Key words: Agri-horti-silvi system, arid, clusterbean, mung bean, productivity.